Let's transform education - Abd Razak, Dzulkifli (2010)
BARCELONA, Spain played host to several key events last week. The United Nations (UN) Decade on Education for Sustainable Development (ESD), which was declared in 2005, has reached its mid-point. Though this has not created a flurry of concern in the Malaysian education scene, it has made an impact internationally. In Barcelona, where architect Antonio Gaudi's designs have almost a total presence, ESD made itself felt.